392 QUALITY OF LIFE AND BURDEN OF DISEASE FOR ADULTS WITH CONGENITAL HEART DISORDERS AND ARRHYTHMIAS. (1st January 2005) - Kirkham, K.; Thordarson, D. S.; Fofonoff, D.; Kiess, M.; Sanatani, S.
Abstract : Background: Advances in surgical techniques and patient care have decreased mortality rates and increased the life expectancy for patients with serious congenital heart abnormalities. These individuals are now commonly living into adulthood following palliative surgeries. As the group of adult congenital heart patients grows, it is increasingly important to quantify the experiences and symptoms that they live with. In order to understand the patient perspective, investigations must explore the impact that increased life expectancy has on the quality of life (QOL) of these individuals. Limited investigations have begun to describe QOL for this population but the impact of specific procedures and complications has not been well described. One frequent complication of palliative surgeries like the Fontan and Mustard procedures is arrhythmia and this investigation explores the impact of this complication on QOL and self-perceived health for these individuals. Methods: Self-perceived health status and quality of life were investigated for 39 patients who had undergone either Fontan or Mustard procedures, and are followed in an adult congenital heart clinic. Patients completed a package that included the Ferrans and Powers Quality of Life Index (QLI) and the Short Form Health Status (SF-36) questionnaires, with additional items designed by the investigators to assess arrhythmia specific symptoms. Results: No significant differences between the diagnostic groups (Mustard and Fontan) or arrhythmia (arrhythmia and nonarrhythmia) groups were found on measures of perceived health (SF-36), quality of life (QLI), or arrhythmia symptoms (dizziness, nausea, and syncope (all p ≥ .05)). Between-groups effect sizes (Cohen's d) for Mustard vs. Fontan and arrhythmia vs. nonarrhythmia were small, indicating that surgical procedure or presence of diagnosed arrhythmia have little effect on patient's perceived quality of life and perceived arrhythmia symptoms. Conclusion: While arrhythmia is a common outcome of some corrective cardiac surgeries for congenital abnormalities, this study indicates that in the adult population, it has little impact on patients' perceived quality of life. These results suggest that current efforts to manage adult congenital heart patients with arrhythmias have been successful at minimizing the impact of their conditions.